Improve Problem-Solving Ability through Implementation of Problem-Based Learning Based on Self-Regulation - Durasa, Helfra; Mertasari, Ni Made Sri; Pujawan, I Gusti Ngurah (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research is motivated by the crucial role of mathematics in human development and the significant challenges faced in mathematics education. The research problem is the low quality of mathematics learning outcomes and the need to improve PSA and self-regulation among students. The purpose of the study was to improve students' Problem-Solving Ability (PSA) through the implementation of Problem-Based Learning (PBL) based on their level of self-regulation. The research design is quantitative quasi-experimental research using a 2 x 2 factorial-level design. The population is 430 seventh-grade students from 1st State High School 1 Langke Rembong. Data analysis using a two-way ANOVA. The results showed that PBL had a positive impact on PSA. In addition, the interaction between learning models and self-regulation significantly affects PSA. These findings have implications for classroom practice, proving the importance of applying PBL to improve PSA and the need to develop student self-regulation. The research also highlights the importance of collaboration between PBL and conventional teaching to improve student learning outcomes in mathematics.